Motives for Exercising and Associations with Body Composition in Icelandic Adolescents - Pablo Galan-Lopez; Francis Ries (MDPI AG, 2019)
The aim of this study is to identify and analyze the motives that lead Icelandic teenagers to engage in physical exercise and the possible associations with variables of their body composition. For this purpose, the Self-Report of Reasons for the Practice of Physical Exercise questionnaire (AMPEF) was administered to 387 students (54% boys and 46% girls, Mage = 13.38 years) from Reykjavik (Iceland). The results reveal the subscales Revitalization and Enjoyment, Strength and Endurance, Challenge and Competition as the main motives for exercising among the participants. Boys score higher in all subscales than girls except for Revitalization and Enjoyment. Associations between the motive Weight Management and Appearance, and BMI and Fat % levels were found. It can be concluded that the participants’ physical exercise practice is based on the feelings and experiences they perceive in the sports practice process.